Madrasah Aliyah's Al-Quran Literacy-Based Needs Analysis and Teacher Competency Strengthening Model - Muhammad Iqbal Humaidi; Abd. Kahar (STAI Syaichona Moh. Cholil Bangkalan, 2024)
The main objective of this article is to explain the model of needs analysis and strengthening of teacher competence based on Quranic literacy in Madrasah Aliyah (Islamic Senior High School). This study employed a qualitative case study approach. The subjects were the principal, vice-principal, and religious education teacher. Data collection involved in-depth interviews, observation, and documentation. Data analysis included data reduction, data presentation, and conclusion drawing. The study concluded that developing teacher competency in Quranic literacy aims to equip teachers with the ability to design literacy instruction and contribute productively to society in line with Quranic values. Strengthening Quranic teacher competency is achieved through training, guidance, resource provision, ongoing guidance and supervision, and the development of a learning community among facilitators.